GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 45290 species occurrences available in GBIF matching the query: TaxonKey: Senecio viscosus L. HasCoordinate: true HasGeospatialIssue: false. The dataset includes 45290 records from 201 constituent datasets: 64 records from Merseyside BioBank (unverified). 4 records from NBIS Records to December 2016. 18 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 1 records from Wicken Fen nature reserve species data held by The National Trust. 13 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 6 records from Phanerogamic Botanical Collections (S). 4 records from Jordal. 5 records from University of Vienna, Institute for Botany - Herbarium WU. 2 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 2 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 172 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 4 records from Online Atlas of vascular plants 2012-2020. 5 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 1 records from Fremmede arter - Planteimport, Engebråten Planteskole. 11 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from PlutoF platform observations. 4 records from LNHG Biological Records Dataset. 1 records from Spredning av fremmede arter med tømmerimport til Norge. 1 records from Berlin-Brandenburg Plant Collection 2005. 325 records from FLORIVON. 229 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 3 records from Karplanter i vernet barskog og edelløvskog. 5 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 132 records from Shropshire Ecological Data Network database. 2475 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 97 records from RECORD Vascular Plant Data. 59 records from BioFokus. 22 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 43 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 3 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 11106 records from Artportalen (Swedish Species Observation System). 2 records from BBOWT Local Wildlife Sites Surveys 1994-2003. 8 records from Stabbetorp - Floristiske registreringer 2016. 13 records from Miscellaneous records held on the Cofnod database. 1 records from Collection botanique Jaubert et Saul (BOUM). 3 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 99 records from Oskarshamn herbarium (OHN). 193 records from Données ONF Faune-Flore-Fonge. 103 records from CSIC-Real Jardín Botánico-Anthos. Sistema de Información de las Plantas de España. 1 records from Herbier de Strasbourg. 62 records from Vascular Plant Herbarium, UiB. 141 records from Hertfordshire Flora Survey Records 1987-2005. 7 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 9 records from iNaturalist Research-grade Observations. 9 records from CONN. 1560 records from Other BSBI Scottish data up to 2012. 2 records from Estonian Museum of Natural History. 1 records from Collection botanique Le Grand A. (BOUM). 2 records from NINA botanical collection. 25 records from National Trust Species Records. 3 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 4 records from Estonian University of Life Sciences. 10 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 19 records from All taxa records for Leicestershire and Rutland between 1987 and 2016. 1 records from Kiesgruben Wemb. 1 records from Schulgarten mit Klasse 8a (Essen). 1 records from Wangerooge. 4 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 1 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 1 records from Industriebrache (Kempen). 1 records from Schulgelände Paul-Gerhardt-Schule. 1 records from Schulzentrum "Parc Hosingen". 7 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 2925 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 4 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 30 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 93 records from SEWBReC Vascular Plants (South East Wales). 115 records from naturgucker. 1 records from RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 2 records from Hatfield Forest species data held by The National Trust.. 1 records from LBV 100 - Artenvielfalt am Rothsee. 1 records from Schatzinsel Norderney. 9 records from Gloucestershire Historic Wildlife Sightings prior to 1st Jan 2000. 1116 records from Dutch Vegetation Database (LVD). 5683 records from INPN - Données flore des CBN agrégées par la FCBN. 14 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 1 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 1 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 1 records from Collection botanique Mulon L. (BOUM). 193 records from Tiroler Landesmuseum Ferdinandeum. 1 records from The Fungal Collection at the Botanische Staatssammlung München. 208 records from IBF Monitoring of Vascular Plants. 53 records from BRERC species records recorded over 15 years ago. 21 records from Natural History Museum (London) Collection Specimens. 3 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 3 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 3 records from Universität Salzburg. 4 records from Canadian Museum of Nature Herbarium. 2 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 13 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 5 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 3 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 2 records from Aranzadi Zientzi Elkartea. 2 records from CIBIO, Alicante:ABH-GBIF. 1 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 1 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 3 records from Institut Botanic de Barcelona, BC. 31 records from Herbarium of Jyväskylä University Museum. 1 records from herbario. 6 records from Botany registration database by Danish botanists. 1 records from GEO Biodiversity Day. 4 records from Herbarium Berolinense. 863 records from Observations du Conservatoire botanique national du Bassin parisien.. 38 records from Biologiezentrum Linz. 5 records from The Erysiphales Collection at the Botanische Staatssammlung München. 3 records from Institut Botanic de Barcelona, BC-Histórico. 8 records from inatura - Erlebnis Naturschau Dornbirn. 4 records from SER Site-based Surveys. 23 records from Biodiversitätsdatenbank des Landes Salzburg. 3 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 1 records from Vascular Plants, Observations, Oslo (O). 2 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from BÜG. 1 records from DJH. 1 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1 records from Gemeinde Sursee. 1 records from Naturschutzgebiet Bausenberg. 1 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 1 records from GEO-Hauptveranstaltung (Duisburg). 1 records from BUND - Dassower See (Lübeck/Dassow). 1 records from Pottundkopp. 1 records from Bergkamen- Bergehalde Großes Holz. 1 records from Lindau im Bodensee. 1 records from Innenstadt Göttingen - Natur Zuhause. 156 records from Vegetation surveys of coastal shingle in Great Britain. 1052 records from Atlas Flora Danica. 787 records from Scottish SNH-funded BSBI records. 2 records from Herbarium of Namur. 17 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 1 records from NRW Regional Data: North Wales. 594 records from Belgian IFBL Flora Checklists (1939-1971). 433 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 1 records from Perchtoldsdorfer Heide. 30 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 119 records from Biological and palaeontological collection and observation data MNHNL. 4 records from Botany Division, Yale Peabody Museum. 7 records from Herbarium Senckenbergianum (FR). 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 5 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from National Wetland Inventory (NV). 273 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 6 records from Flora d'Andorra. 91 records from Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 1 records from ArtenFinder. 354 records from Lund Botanical Museum (LD). 1 records from Berlin-Brandenburg Plant Collection 2004. 9 records from Natural Resources Wales Regional Data : Mid-Wales. 730 records from Norwegian Species Observation Service. 4 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 1 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 691 records from LERN Records. 6 records from Spredning av fremmede arter med planteimport til Norge. 152 records from Carnet en Ligne. 9 records from SER Species-based Surveys. 9 records from ARKO kulturmarkseng. 7 records from All observations extracted from the Flora of Northumberland and Durham 1831. 508 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 17 records from TWIC Biodiversity Field Trip Data (1995-2014). 1 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 5 records from Merseyside BioBank (verified). 2 records from Herbier du Québec (QUE) - Collection de plantes vasculaires. 402 records from Flora of Worcestershire. 3 records from Estonian Nature Observations Database. 56 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 1 records from Kartlegging av dragehode. 10 records from Vascular plant herbarium, Tromsø Museum. 167 records from Vascular plant herbarium, NTNU University Museum. 193 records from Données ONF Faune-Flore-FOnge. 511 records from Vascular Plants, Field notes, Oslo (O). 18 records from Stoke-on-Trent Environmental Survey results (1982-1984). 52 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 9 records from Distribution of Higher Plants in Greater Manchester. 20 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 10 records from Green Plant Herbarium (TRT). 33 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 1 records from Stackpole National Nature Reserve Species Inventory and Ad Hoc sightings from around Pembrokeshire. 1 records from Miscellaneous Vascular Plants. 462 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 1 records from Herbarium of University of Białystok - Vascular Plants. 17 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 1 records from BioFresh Pond Data. 323 records from Vascular Plant Herbarium, Oslo (O). 1 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 2 records from Local Wildlife Site Surveys Oxfordshire. 7245 records from Flora von Deutschland (Phanerogamen). 14 records from Vascular plants of Amrum 2007-2008. 424 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 38 records from E. C. Smith Herbarium (ACAD). 1 records from Natagriwal ; Observations made from operations within Natura 2000 habitats and other semi-natural areas. 2 records from SWECO. 1 records from National Trust for Scotland Species Records. 20 records from Vascular plant field notes, NTNU University Museum. 1 records from Vascular plants in Danish coastal meadows. 1 records from SysTax - Herbaria. 416 records from Welsh BSBI data (ex-VPDB dataset) at hectad resolution. 3 records from Nijmegen Natural History Museum (NL) - Herbarium. 6 records from BRERC species records within last 15 years. 18 records from Flora of the Stołowe Mts.. 53 records from Atlas des plantes vasculaires de Lorraine. 29 records from Vascular Plant Records up to 2010. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences